Konsep Ekonomi Islam Versi Al-Mawardi dan Al-Ghazali - fatimah, emi sri rahayu; Masse, Rahman Ambo; Kara, Muslimin (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2024)
ABSTRACT This article discusses the concepts of Islamic economic thought according to Al-Mawardi and Al-Ghazali. The purpose of this article is to study the economic thinking of Muslim scholars who lived during the Abbasid dynasty, namely Al-Mawardi and al-Ghazali. The research method used in writing this article is literature review. Literature reviews are used to analyze previous research related to the topic in this article. The research results obtained show that Al-Mawardi and Al-Ghazali through their thinking have studied Islamic economics comprehensively by showing that Al-Mawardi's thoughts about the state and economic activity, the concept of public loans, taxation, the urgency of state financial institutions (baitul maal), and the concept of justice is still very relevant in the current context.Then, Al-Ghazali's economic analysis focuses on a number of topics, such as the development of trade and markets, production, barter, and money, and the role of government and public finance. Meanwhile, Al-Ghazali's economic theory begins with the idea of maslahah which covers all human endeavors and establishes strong ties between humans and society.